2009
DOI: 10.1068/p5886
|View full text |Cite
|
Sign up to set email alerts
|

Age Effects on the Perception of Motion Illusions

Abstract: Anomalous motion illusions represent a popular class of illusions and several studies have made an effort to explain their perception. However, understanding is still inconsistent. Age-related differences in susceptibility to illusory motion may contribute to further clarification of the underlying processing mechanisms. We investigated the effect of age on the perception of four different anomalous motion illusions. The Enigma illusion, the Rotating-Snakes illusion, the Pinna illusion, and the Rotating-Tilted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
30
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(34 citation statements)
references
References 80 publications
4
30
0
Order By: Relevance
“…By contrast, the streaming in the Enigma illusion did not apparently decrease, and the Ouchi illusion was even enhanced by adding smooth motion. The present results, showing differences in the time courses of perceived motion in the illusions, are consistent with the previous results (Billino et al, 2009;Tomimatsu et al, 2010).…”
Section: Ouchi and Enigma Illusionssupporting
confidence: 82%
See 2 more Smart Citations
“…By contrast, the streaming in the Enigma illusion did not apparently decrease, and the Ouchi illusion was even enhanced by adding smooth motion. The present results, showing differences in the time courses of perceived motion in the illusions, are consistent with the previous results (Billino et al, 2009;Tomimatsu et al, 2010).…”
Section: Ouchi and Enigma Illusionssupporting
confidence: 82%
“…They suggested that the direction of the perceived motion is from black, to dark gray, white, and light gray-a luminance profile that, for example, produced the "Rotating Snakes" (Kitaoka, 2003) illusion. Studies have quantitatively confirmed that the motion in this illusion appears more in peripheral vision (Beer, Heckel, & Greenlee, 2008;Hisakata & Murakami, 2008) and that the illusion is weaker for senior observers (Billino, Hamburger, & Gegenfurtner, 2009). One characteristic common to both the FW illusion and the modified FW illusion is that steady fixation weakens the illusory motion, and eventually halts it within several seconds.…”
mentioning
confidence: 57%
See 1 more Smart Citation
“…Similarly, center-surround contextual effects such as the tilt illusion are also altered in older adults. 37 The majority of these studies were performed with central fixation rather than in the parafovea as here. The parameter space for exploring these types of perceptual phenomena is very large, and the mechanisms of some effects are more established from a neurophysiologic perspective than others.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, there is considerable debate among investigators as to whether gaze instability is strictly necessary to the illusory motion perception or, rather, if fixational eye movements only improve the strength of the illusion. Interestingly, not all subjects report perceiving illusory motion2223. The origin of this polymorphic response is not entirely clear, but Fraser and Wilcox22 reported a significant parent-offspring correlation in the response to a motion illusion indicating either a genetic causation or a common environment effect.…”
mentioning
confidence: 99%